Beyond the Medical Record: Other Modes of Error Acknowledgment - Rosenthal, Marilynn M (Blackwell Science Inc, 2005)
BACKGROUND: Studies before and since the 1999 Institute of Medicine report have noted the limitations of using medical record reporting for reliably quantifying and understanding medical error. Quantitative macro analyses of large datasets should be supplemented by small-scale qualitative studies to provide insight into micro-level daily events in clinical and hospital practice that contribute to errors and adverse events and how they are reported. DESIGN: The study design involved semistructured face-to-face interviews with residents about the medical errors in which they recently had been involved and included questions regarding how those errors were acknowledged. OBJECTIVE: This paper reports the ways in which medical error is or is not reported and residents' responses to a perceived medical error. PARTICIPANTS: Twenty-six residents were randomly sampled from a total population of 85 residents working in a 600-bed teaching hospital. MEASUREMENTS: Outcome measures were based on analysis of cases residents described. Using Ethnograph and traditional methods of content analysis, cases were categorized as Documented, Discussed, and Uncertain. RESULTS: Of 73 cases, 30 (41.1%) were formally acknowledged and Documented in the medical record; 24 (32.9%) were addressed through Discussions but not documented; 19 cases (26%) cases were classified as Uncertain. Twelve cases involved medication errors, which were acknowledged in different categories. CONCLUSIONS: The supervisory discussion, the informal discussion, and near-miss contain important information for improving clinical care. Our study also shows the need to improve residents' education to prepare them to recognize and address medical errors.